Implementation of Individual Conversion Therapy to Reduce Auditory Hallucinations with Paranoid Schizophrenia : A Case Study - Asep Gunawan; Meida Bintari Janatunnisa (Inspirasi Foundation, 2024)
Introduction: Auditory hallucinations are a perceptual condition that causes sounds that do not actually exist to appear to be heard. One method for treating people with auditory hallucinations is one-way conversation therapy. Individual Conversation Therapy is a better alternative therapy for people who experience hallucinations because it provides more meaningful evaluation findings. Objective: Provide care and provide a thorough explanation regarding Individual Conversation Therapy therapy for reducing sensory perception disorders including auditory hallucinations. Method: This research uses a nursing care strategy, with a descriptive case study design, on Mr. R, 23 years old who experiences auditory hallucinations based on inclusion and exclusion criteria. The data collection process was carried out through interviews using Individual Conversation Therapy techniques, observation and documentation. Result: Based on the case study findings, the patient stated that he was able to improve his hallucinations during Individual Conversation Therapy treatment, indicating that the intervention was effective. Conclusion: The conclusion of nursing care for sufferers of sensory perception disorders (hearing) in patients with hallucinations, the implementation of Individual Conversation Therapy is recommended because the effect of this therapy can reduce hallucinatory sounds. Introduction: Auditory hallucinations are a perceptual condition that causes sounds that do not actually exist to appear to be heard. One method for treating people with auditory hallucinations is one-way conversation therapy. Individual Conversation Therapy is a better alternative therapy for people who experience hallucinations because it provides more meaningful evaluation findings. Objective: Provide care and provide a thorough explanation regarding Individual Conversation Therapy therapy for reducing sensory perception disorders including auditory hallucinations. Method: This research uses a nursing care strategy, with a descriptive case study design, on Mr. R, 23 years old who experiences auditory hallucinations based on inclusion and exclusion criteria. The data collection process was carried out through interviews using Individual Conversation Therapy techniques, observation and documentation. Result: Based on the case study findings, the patient stated that he was able to improve his hallucinations during Individual Conversation Therapy treatment, indicating that the intervention was effective. Conclusion: The conclusion of nursing care for sufferers of sensory perception disorders (hearing) in patients with hallucinations, the implementation of Individual Conversation Therapy is recommended because the effect of this therapy can reduce hallucinatory sounds.